THE AFFECTIVE INERTIA OF WOMEN WITH HIGHER EDUCATION: overwork, unfulfilled affective trajectories and emotional harm - Jardim, Maria Chaves [UNESP]; de Souza, Thaís Caetano [UNESP] (Universidade Federal da Bahia, 2025)
Studies on love have grown over the years, highlighting the centrality that the topic has gained in contemporary society. In this study agenda, a topic that has been little studied is the absence or deprivation of love. In this article, we seek to objectify the deprivation of love from a group of single heterosexual women aged 40 and with a higher education degree. Our methodological strategy was virtual immersion based on a course on relationships and the reconstruction of the emotional trajectory of two women. The data indicate that these women are part of a generation that invested in their careers and, therefore, had a rupture in their emotional trajectory when they transgressed one of the main rules in the field of love: marriage. Furthermore, excessive work would help to emotionally isolate these women, who begin to suffer emotional losses as a result of emotional deprivation.
L’INERTIE AFFECTIVE DES FEMMES DIPLOMEES DE L’ENSEIGNEMENT SUPERIEUR: excès de travail, trajectoires affectives non réalisées et préjudices émotionnels
A INÉRCIA AFETIVA DE MULHERES COM DIPLOMA DE ENSINO SUPERIOR: excesso de trabalho, trajetórias afetivas não realizadas e prejuízos emocionais
Keywords: Career; Emotional harm; Love; Trajectory not completed; Work